Phraseological units with the color terms ‘white’ and ‘black’ in mass media headlines - Liliia K. Khalitova; Diana V. Solovieva (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. The use of phraseological units with a color term in mass media headlines has become a common practice among journalists in order to attract the audience’s attention to the published material. However, the incorrect use of such means of language entails risks, such as clichés, misunderstanding and ambiguity. The authors demonstrate the relevance of using phraseological units with the color terms ‘white’ and ‘black’ in media headlines. Purpose – to claim the relevance of usage of phraseological units with color terms ‘white’ and ‘black’ in media headlines. Materials and methods. The research methods include contextual and quantitative analysis. The article is based on media materials for the period 2024-2025 published on the news platform Yandex Dzen and online press archives. The research material was obtained by a continuous sampling of headlines containing phraseological units with the color terms ‘white’ and ‘black’ (N=204 headlines). In order to identify and describe phraseological units the Phraseological Dictionary of the Russian literary language by A.I. Fedorov was used. Results. The study proves that the use of phraseological units with the color terms ‘white’ and ‘black’ in media headlines creates expressiveness, intrigue and thus increases a reader’s willingness to read the text. Quantitative analysis demonstrates the frequent use of these units in mass media headlines. Moreover, color terms being concise have a great potential for wordplay and can convey the author’s ideas implicitly. Contextual analysis shows that out of 204 headlines containing phraseological units with the color terms "white" and "black", 171 (84%) headlines reflect negative news. Actualization of the negative connotation in the studied phraseological units reveals implicit meanings and enhances the overall negative coloring of the message. Practical implications. The results of the study can be used in the field of media communication, teaching linguistics, lexicology and stylistics. The obtained data can be useful for journalists in developing effective strategies to influence the audience.